Musical Works of Hieromonk Neophytus of Rila - Касабов, Андрей (Forum Theologicum Sardicense, 2025)
Andrey Kasabov, Musical Works of Hieromonk Neophytus of Rila. The present article traces the life and work of the eminent figure of the Bulgarian Revival, Monk Neophytus of Rila. The facts are organized according to the research conducted since the late 19th century, as well as some of the personal writings of Father Neophytus. The article describes the main aspects of his musical creativity and places special emphasis on his contributions to the musical traditions of the Rila Monastery School and the Patriarchal School of Theology at the Monastery of the Holy Trinity on the island of Halki. His personal compositions and translated musical works are presented based on manuscript collections from the library of the Rila Monastery.